1998
DOI: 10.1111/1468-0084.00103
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Labour Supply and Child Nutrition in West Africa

Abstract: It is widely recognized that women in developing countries have dual roles as generators of household income and as primary caregivers to their children. Many policies directed at reducing poverty or malnutrition involve one or the other of these roles. Programs to reduce child malnutrition, for example, typically target mothers as caregivers. However, because of the time constraints women face, there are potential conflicts between women's different activities about which policy makers are rarely informed. Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 19 publications
(31 reference statements)
8
60
0
Order By: Relevance
“…The Bangladesh study showed that chances for survival for female children were very low as compared to males due to factors such as food sharing practices in the household. This is in line with [22], who found out that the female child had less nutritional status as compared to their male counterparts attributing to the possibility of discriminatory behaviour which favours males [26]. [27] revealed gender as a determinant of underweight as male children were more likely to be underweight as compared to their females.…”
Section: Socio-demographic Factorssupporting
confidence: 79%
See 2 more Smart Citations
“…The Bangladesh study showed that chances for survival for female children were very low as compared to males due to factors such as food sharing practices in the household. This is in line with [22], who found out that the female child had less nutritional status as compared to their male counterparts attributing to the possibility of discriminatory behaviour which favours males [26]. [27] revealed gender as a determinant of underweight as male children were more likely to be underweight as compared to their females.…”
Section: Socio-demographic Factorssupporting
confidence: 79%
“…This study showed that most caregivers had primary level of education and a few having reached secondary level. In some study, 46% caregivers had primary level and only 2% having secondary level [26]. According to Schnepf [25], caregiver education potrays the intellectual environment in which children are growing.…”
Section: Caregiver Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Parental migration is likely to affect the time and labour allocation in both productive and reproductive activities, including home production and time spent in childcare (Stark and Bloom 1985;Glick and Sahn 1998). Thus, the parent's labour migration, which reduces the time available for the household activities related to child development, may place young children at a nutritional risk (Swart 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Empirical research on the influence of maternal work on child nutrition is ambiguous (see Leslie, 1988 andGlick andSahn, 1995). However, given the traditional role of women in Bangladeshi society, it is likely that working women come from less affluent households.…”
Section: Datamentioning
confidence: 99%